Moderated Mediation Model of Interrelations between Workplace Romance, Wellbeing, and Employee Performance - Khan, Muhammad Aamir Shafique; Jianguo, Du; Usman, Muhammad; Ahmad, Malik I. (Frontiers in Psychology, 2017)
In this study, first we examined the effect of workplace romance on employee job performance, and the mediatory role of psychological wellbeing in the relationship between workplace romance and employee performance. Then we tested the moderating effects of gender and workplace romance type – lateral or hierarchical – on the indirect effect of workplace romance on employee performance. Based on a survey of 311 doctors from five government teaching hospitals in Pakistan, we used structural equation modelling and bootstrapping to test these relationships. This study reveals that psychological wellbeing significantly fully mediates the positive relationship between workplace romance and job performance. Moreover, multi-group analysis shows that gender moderates the indirect effect of workplace romance on employee performance, where the indirect effect of workplace romance on employee performance is stronger for male participants. This study carries important implications, particularly for the policy makers and managers of healthcare sector organizations.